FOXN1: A Master Regulator Gene of Thymic Epithelial Development Program - Romano, Rosa; Palamaro, Loredana; Fusco, Anna; Giardino, Giuliana; Gallo, Vera; Del Vecchio, Luigi; Pignata, Claudio (Frontiers in Immunology, 2013)
T cell ontogeny is a sophisticated process, which takes place within the thymus through a series of well-defined discrete stages. The process requires a proper lympho-stromal interaction. In particular, cortical and medullary thymic epithelial cells (cTECs, mTECs) drive T cell differentiation, education and selection processes, while the thymocyte-dependent signals allow TECs to maturate and provide an appropriate thymic microenvironment. Alterations in genes implicated in thymus organogenesis, including Tbx1, Pax1, Pax3, Pax9, Hoxa3, Eya1 and Six1, affect this well-orchestrated process, leading to disruption of thymic architecture. Of note, in both human and mice, the primordial TECs are yet unable to fully support T cell development and only after the transcriptional activation of the Forkhead-box n1 (FOXN1) gene in the thymic epithelium this essential function is acquired. FOXN1 is a master regulator in the TEC lineage specification in that it down-stream promotes transcription of genes, which, in turn, regulate TECs differentiation. In particular, FOXN1 mainly regulates TEC patterning in the fetal stage and TEC homeostasis in the postnatal thymus. An inborn null mutation in FOXN1 leads to Nude/SCID phenotype in mouse, rat and humans. In Foxn1-/- nude animals, initial formation of the primordial organ is arrested and the primordium is not colonized by hematopoietic precursors, causing a severe primary T cell immunodeficiency. In humans, the Nude/SCID phenotype is characterized by congenital alopecia of the scalp, eyebrows, and eyelashes, nail dystrophy and a severe T cell immunodeficiency, inherited as an autosomal recessive disorder. Aim of this review is to summarize all the scientific information so far available to better characterize the pivotal role of the master regulator FOXN1 transcription factor in the TEC lineage specifications and functionality.